The dietary inflammatory index and its association with the prevalence of hypertension: A cross-sectional study - Zhou, Nan; Xie, Zhi-Ping; Liu, Qing; Xu, Yun; Dai, Si-Cheng; Lu, Juan; Weng, Jia-Yi; Wu, Li-Da (Frontiers in Immunology, 2023)
Aims We aim to investigate the association of the Dietary Inflammatory Index (DII) with the prevalence of hypertension in a large multiracial population in the United States. Methods Participants from the National Health and Nutrition Examination Survey (NHANES) (1999–2018) were included in this cross-sectional study. Dietary information was obtained and used to calculate DII. Blood pressures of participants were measured by experienced examiners. The NHANES used the method of “stratified multistage probability sampling,” and this study is a weight analysis following the NHANES analytic guidance. Weight logistic regression analysis was adopted to investigate the association of hypertension with DII. Least Absolute Shrinkage and Selection Operator (LASSO) regression was carried out to screen the most important dietary factors associated with the risk of hypertension. Moreover, a nomogram model based on key dietary factors was established; the receiver operating characteristic (ROC) curve was used to evaluate the diagnostic power of the nomogram model for screening hypertension risk. Results A total of 45,023 participants were included in this study, representing 191 million residents in the United States. Participants with hypertension had an elevated DII compared with those without hypertension. Weight logistic regression showed that an increment of DII was strongly associated with hypertension after adjusting for confounding factors. The nomogram model, based on key dietary factors screened by LASSO regression, showed a favorable discriminatory power with an area under the curve (AUC) of 78.5% (95% CI: 78.5%–79.3%). Results of the sensitivity analysis excluding participants who received any drug treatment were consistent with those in the main analysis. Conclusion An increment of DII is associated with the risk of hypertension. For better prevention and treatment of hypertension, more attention should be paid to controlling dietary inflammation.